CABG versus PCI in the Treatment of Unprotected Left Main Disease in Diabetics: A Literature Review - Lambert, Daniel; Mattia, Allan; Hsu, Angel; Manetta, Frank (International Journal of Angiology, 2021)
The approach to left main coronary artery disease (CAD) in diabetic patients has been extensively debated. Diabetic patients have an elevated risk of left main disease in addition to multivessel disease. Previous trials have shown increased revascularization rates in percutaneous coronary intervention compared with coronary artery bypass grafting (CABG) but overall comparable outcomes, although many of these studies were not using the latest stent technology or CABG with arterial revascularization. Our aim is to review the most recent trials that have recently published long-term follow-up, as well as other literature pertaining to left main disease in diabetic patients. Furthermore, we will be discussing some future treatment strategies that could likely create a paradigm shift in how left main CAD is managed.
Keywords: PCI; CABG; left main coronary artery disease; stent; acute coronary syndrome; coronary intervention; cardiac